Heterovalent cation substitutional doping for quantum dot homojunctions - Stavrinadis, Alexandros; Rath, Arup Kumar; Pelayo Garcia de Arquer, F.; Diedenhofen, Silke L.; Magen, Cesar; Martinez, Luis; So, David; Konstantatos, Gerasimos (Nature Communications, 2013)
Colloidal quantum dots have emerged as a material platform for low-cost high-performance optoelectronics. At the heart of optoelectronic devices lies the formation of a junction, which requires the intimate contact of n-type and p-type semiconductors. Doping in bulk semiconductors has been largely deployed for many decades, yet electronically active doping in quantum dots has remained a challenge and the demonstration of robust functional optoelectronic devices had thus far been elusive. Here we report an optoelectronic device, a quantum dot homojunction solar cell, based on heterovalent cation substitution. We used PbS quantum dots as a reference material, which is a p-type semiconductor, and we employed Bi-doping to transform it into an n-type semiconductor. We then combined the two layers into a homojunction device operating as a solar cell robustly under ambient air conditions with power conversion efficiency of 2.7%.